Mucormycosis in a diabetic patient: A case report with an insight into its pathophysiology - Syeda Neelam Afroze; Rajani Korlepara; Guttikonda Venkateswara Rao; Jayakiran Madala (Wolters Kluwer Medknow Publications, 2017)
Mucormycosis is one of the most rapidly progressing and fulminant forms of fungal infection which usually begins in the nose and paranasal sinuses following inhalation of fungal spores. It is caused by organisms of the subphylum Mucormycotina, including genera as Absidia, Mucor, Rhizomucor, and Rhizopus. The incidence of mucormycosis is approximately 1.7 cases per 1,000,000 inhabitants per year. Mucormycosis affecting the maxilla is rare because of rich blood vessel supply of maxillofacial areas although more virulent fungi such as Mucor can overcome this difficulty. The common form of this infection is seen in the rhinomaxillary region and in patients with immunocompromised state such as diabetes. Hence, early diagnosis of this potentially life-threatening disease and prompt treatment is of prime importance in reducing the mortality rate.